Macro-economic determinants of the IPO waves: An assessment of G-7 countries [version 2; peer review: 1 approved, 2 approved with reservations, 1 not approved] - Esin Benhür Aktürk; MUSTAFA ÖZYEŞİL (F1000Research)
Background The objective of this study is to explore the macroeconomic factors considered by companies in scheduling initial public offerings (IPOs). Methods The panel data analysis method was employed to investigate the relationship between the frequency of IPOs and selected macroeconomic indicators within the stock markets of G-7 countries spanning from 1999 to 2020. An econometric model utilizing a random effect approach was utilized, employing the Driscoll-Kraay resistant standard estimator to address deviations. Results The analysis revealed that stock market returns exert a statistically significant positive influence on the volume of public offerings. Conclusions Based on these findings, it can be inferred that companies strategically time their IPOs during periods characterized by relatively high stock market returns.